Tutorial on Monoclonal Antibody Pharmacokinetics and Its Considerations in Early Development - Ovacik, Meric; Lin, Kedan (Clinical and translational science, 2018)
The tutorial introduces the readers to the fundamentals of antibody pharmacokinetics (PK) in the context of drug development. Topics covered include an overview of antibody development, PK characteristics, and the application of antibody PK/pharmacodynamics (PD) in research and development decision‐making. We also discuss the general considerations for planning a nonclinical PK program and describe the types of PK studies that should be performed during early development of monoclonal antibodies.